Conventional MRI scan and DTI imaging show more severe brain injury in neonates with hypoxic-ischemic encephalopathy and seizures. (July 2018) - Kline-Fath, Beth M.; Horn, Paul S.; Yuan, Weihong; Merhar, Stephanie; Venkatesan, Charu; Thomas, Cameron W.; Schapiro, Mark B.
Abstract: Background: Neonates with hypoxic-ischemic encephalopathy (HIE) and seizures have poorer outcome for undetermined reasons. Aims: Our aim was to determine if brain imaging was more abnormal in neonates with HIE and electrographically confirmed seizures and whether this was impacted by seizure burden. Study design: Single center retrospective review. Subjects: Forty-eight term neonates with HIE (with and without seizures) underwent MRI brain scans before age 14 days between the years 2008 and 2013. Outcome measures: Images were rated using a MRI injury score and fractional anisotropy (FA) values were extracted from diffusion tensor imaging (DTI). Results: The seizure group (n = 25) had significantly more injury within white matter, basal ganglia, posterior limb of internal capsule, and watershed areas compared to the group without seizures (n = 23). The severity of injury in all measured areas increased with increasing seizure severity. The seizure group also had lower FA values in posterior limb of the internal capsule and the splenium of corpus callosum. Conclusions: Neonates with HIE and seizures had more brain injury that occurred in areas typically affected by HIE and was greater with higher seizure burden. Seizures may be a marker of more severe brain injury or seizures themselves may amplify brain damage from HIE.